Reanimating orality. The case for a new Bible translation in Southern Sotho - Naudé, Jacobus A. (Old Testament essays, 2006)
The purpose of this paper is to suggest a means of translating the Bible to provide for the needs of a community consisting largely of members not able to read written texts. The Southern Sotho community uses either the 1909 (with various revisions) or 1989 translation of the Southern Sotho Bible. The former is the product of the word for word approach to translation. The primary concern of the latter was meaning and readability. Both translations lean heavily on the reader's ability to understand a written text. In view of the fact that the Southern Sotho religious community consists preponderantly of members not able to read written texts the authors felt themselves compelled to suggest another vehicle for the transfer of religious thought in Bible translation. Pivotal to this paper is the issue of translation strategy as applicable to the particular audiences in question. Consequently, this paper argues for a rhythmical and sonorous translation, which is clearly audible and understandable.